The Effectiveness of the Integrated Criminal Justice System in Handling Minor Criminal Offenses from a Restorative Justice Perspective - Hani, Hani Irhamdessetya (Yayasan Meira Visi Persada, 2026)
Abstract The Integrated Criminal Justice System (ICJS) is designed to ensure effective, efficient, and just criminal law enforcement through institutional coordination among law enforcement agencies. However, in practice, the handling of minor criminal offenses in Indonesia remains dominated by a formalistic and retributive approach, which often fails to reflect substantive justice and social restoration. This study aims to examine the effectiveness of the ICJS in handling minor criminal offenses and to evaluate its performance from a restorative justice perspective. The research employs a normative juridical method using statutory and conceptual approaches, supported by limited empirical data to strengthen the analysis. The findings reveal that although normative frameworks provide mechanisms for expedited proceedings and restorative justice-oriented policies, their implementation within the ICJS remains fragmented and insufficiently integrated across all stages of the criminal justice process. As a result, the effectiveness of the ICJS tends to be procedural rather than substantive, with restorative justice functioning as an exception rather than a systemic paradigm. This study concludes that the limited integration of restorative justice undermines the achievement of proportionality, efficiency, and social restoration in minor criminal cases. The research underscores the urgency of systemically integrating restorative justice into the ICJS to enhance substantive justice, reduce procedural inefficiencies, and strengthen social harmony. This study contributes original insights by positioning restorative justice as a central evaluative framework for assessing the effectiveness of the ICJS, offering policy-relevant implications for criminal justice reform. Keywords: integrated criminal justice system, minor criminal offenses, restorative justice, substantive justice